Topical and systemic GLP-1R agonist administration both rescue retinal ganglion cells in hypertensive glaucoma - Lawrence, Emily C. N.; Guo, Michelle; Schwartz, Turner D.; Wu, Jie; Lu, Jingwen; Nikonov, Sergei; Sterling, Jacob K.; Cui, Qi N. (Frontiers in Cellular Neuroscience, 2023)
Glaucomatous neurodegeneration, a blinding disease affecting millions worldwide, has a need for the exploration of new and effective therapies. Previously, the glucagon-like peptide-1 receptor (GLP-1R) agonist NLY01 was shown to reduce microglia/macrophage activation, rescuing retinal ganglion cells after IOP elevation in an animal model of glaucoma. GLP-1R agonist use is also associated with a reduced risk for glaucoma in patients with diabetes. In this study, we demonstrate that several commercially available GLP-1R agonists, administered either systemically or topically, hold protective potential in a mouse model of hypertensive glaucoma. Further, the resulting neuroprotection likely occurs through the same pathways previously shown for NLY01. This work contributes to a growing body of evidence suggesting that GLP-1R agonists represent a viable therapeutic option for glaucoma.